2018
DOI: 10.1038/s41598-018-28378-x
|View full text |Cite
|
Sign up to set email alerts
|

Black-headed gulls synchronise their activity with their nearest neighbours

Abstract: Animals in groups can benefit from synchronising their behaviour, where multiple individuals conduct similar activities at the same moment in time. Previous studies have demonstrated that some species show synchronisation of vigilance behaviour, but have not explored the mechanism driving this behaviour. Synchronisation could be driven by animals copying their closest neighbours, which would mean that close proximity should lead to increased synchronisation. We simultaneously observed the behaviour of multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…It is also interesting to note that isolates from black-headed gull from different years may be closer to each other than with other sources (for example ST145 isolates), suggesting that the same L. monocytogenes population may be maintained in the black-headed gull population or the black-headed gulls may obtain L. monocytogenes from the same source in different years. Both scenarios are possible considering that black-headed gulls are territorial with lifespan of up to 30 years and may pass through the same locale every year [41]. It has been shown that L. monocytogenes can persist in birds for long periods of time by carriage [42].…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note that isolates from black-headed gull from different years may be closer to each other than with other sources (for example ST145 isolates), suggesting that the same L. monocytogenes population may be maintained in the black-headed gull population or the black-headed gulls may obtain L. monocytogenes from the same source in different years. Both scenarios are possible considering that black-headed gulls are territorial with lifespan of up to 30 years and may pass through the same locale every year [41]. It has been shown that L. monocytogenes can persist in birds for long periods of time by carriage [42].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, this requirement might not even be possible, e.g., for herds that are confined to a plane where observation of distant members is obscured or for very large animal groups in general. The attention toward neighbors is accounted for by most models of collective behavior in animal groups, which, considering local interactions (Vicsek et al, 1995 ; Cucker and Smale, 2007 ; Wang and Lu, 2019 ), are able to capture the synchronization of animals to their neighbors as found for red deer (Rands et al, 2014 ) and recently for black-headed gulls (Evans et al, 2018 ). In a more extreme example, mosquitofish were shown to only respond to their single nearest neighbor (Herbert-Read et al, 2011 ).…”
Section: Interaction Length Vs Correlation Lengthmentioning
confidence: 99%
“…Obviously, this requirement might not even be possible, e.g., for herds that are confined to a plane where observation of distant members is obscured or for very large animal groups in general. The attention towards neighbors is accounted for by most models of collective behavior in animal groups, which, considering local interactions (Vicsek et al, 1995;Cucker and Smale, 2007;Wang and Lu, 2019), are able to capture the synchronization of animals to their neighbors as found for red deer (Rands et al, 2014) and recently for black-headed gulls (Evans et al, 2018). In a more extreme example, mosquitofish were shown to only respond to their single nearest neighbor (Herbert-Read et al, 2011).…”
Section: Interaction Length Versus Correlation Lengthmentioning
confidence: 99%